If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 3y = 17 Solving 2x + 3y = 17 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3y' to each side of the equation. 2x + 3y + -3y = 17 + -3y Combine like terms: 3y + -3y = 0 2x + 0 = 17 + -3y 2x = 17 + -3y Divide each side by '2'. x = 8.5 + -1.5y Simplifying x = 8.5 + -1.5y
| a^2+6a-86=5 | | k^2-2k-32=3 | | 7x^2+4y=28 | | 0=12x^2-35x-18 | | x^2-2-2=0 | | x^2+16x+51=-4 | | =9(9+3h)-4 | | n^2-8n-65=5 | | 2x+16=-56 | | p^2-20p+97=6 | | 4m^2-28m+49=0 | | a=-5a | | -3x-6y=18 | | X+3x+5=22 | | n^2+10n-30=0 | | 4(2x+12)=3(-x+5) | | 7-0.11k=32 | | (64y^3-8)=0 | | 9+n-4=12 | | 3x^2+18x+24=0 | | 9p-17=p+21 | | 4y^2+14y+6= | | 4*8+2*2=80 | | 2(b+4)=6 | | 6n-9=-15 | | 3y^2-4y^3-6y^2+6y^3= | | 4-x+2(5x-6)=-3x-39 | | (2h^2-9h-18)=0 | | 3+4n=5 | | 3(5-4)=80-2(35+1) | | 56z^2+2=22z | | 10x+48x=40(4x-48) |